Relative efficacy of tranexamic acid and preoperative anemia treatment for reducing transfusions in total joint arthroplasty. Issue 3 (17th December 2016) - Styron, Joseph F.; Klika, Alison K.; Szubski, Caleb R.; Tolich, Deborah; Barsoum, Wael K.; Higuera, Carlos A.
Abstract : BACKGROUND: This study aimed to evaluate the efficacy of a perioperative blood management (PBM) protocol at a large, tertiary hospital at reducing blood transfusions after total hip or knee arthroplasty (THA or TKA). STUDY DESIGN AND METHODS: A retrospective review of the PBM for patients undergoing THA or TKA was performed. Adjusted multiple logistic and Poisson regression models examined the effect of patient characteristics and preoperative, intraoperative, and postoperative factors on the likelihood of transfusion and units transfused. RESULTS: Of 883 study patients, 330 (37.4%) had surgery before PBM protocol implementation and served as the control population while 553 (62.6%) were eligible for the protocol. Having a higher preoperative hemoglobin (Hb) was independently associated with a decreased odds of transfusion (odds ratio [OR], 0.480; p < 0.001). Preoperative treatment for anemia (88 [15.9%] patients) did result in a significant, yet modest, increase in preoperative Hb (11.92 g/dL to 12.35 g/dL; p < 0.001) but treatment was not a significant predictor of transfusion. Receiving intraoperative tranexamic acid (TXA; 204 [36.9%] patients) had the greatest effect in reducing the odds of transfusion (OR, 0.289; p < 0.001) and the number of units transfused (−0.6; p = 0.008). CONCLUSION: Having a decreased Hb was shown to be an independent risk factor both for requiring a perioperative blood transfusion and for the volume of transfusion. The very modest increase in Hb achieved by the costly and time‐consuming preoperative anemia optimization program, however, may not be justified when the use of intraoperative TXA led to drastic reductions in both transfusions and transfusion volumes.